1993
DOI: 10.1111/j.1755-3768.1993.tb04650.x
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of sodium iodate injection on ERG in mice

Abstract: The electroretinogram (ERG) was recorded in 15 ICR albino mice before and 2, 4 and 24 h after injection of 40 mg/kg of NaIO3 and the results were compared with the corresponding ultrastructural findings. Both a- and b-wave amplitudes decreased at 2 h after injection and increased at 4 h to the levels before injection and further increased at 24 h after injection. The b-wave threshold intensity increased by 2.1 log units at 2 h after injection. Thereafter, it decreased once at 4 h and significantly increased at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Using a sodium iodate (NaIO 3 )-induced mouse model of AMD [24][25][26], we recently showed that treatment with antithyroid drug protected RPE and photoreceptors from oxidative damage and cell death/necroptosis and preserved retinal function [27]. The present work expanded this research by investigating the involvement of TH receptors (THRs) and the contribution of the receptor subtypes.…”
Section: Introductionmentioning
confidence: 79%
“…Using a sodium iodate (NaIO 3 )-induced mouse model of AMD [24][25][26], we recently showed that treatment with antithyroid drug protected RPE and photoreceptors from oxidative damage and cell death/necroptosis and preserved retinal function [27]. The present work expanded this research by investigating the involvement of TH receptors (THRs) and the contribution of the receptor subtypes.…”
Section: Introductionmentioning
confidence: 79%
“…This effect is not noted in the literature, except by Sato's group, which identified supernormal transient b-waves in NaIO 3 -treated mice. [44][45][46] We extended the observations from Sato et al to include earlier times after injection, lower doses of NaIO 3 , and additional mouse strains. We further found that scotopic a-, b-, and c-waves all transiently increase, and outcomes vary with strain and with the time of assessment, after injection.…”
Section: Discussionmentioning
confidence: 99%
“…27 Intravitreal and systemic injection of sodium iodate in mice, cats, and rabbits has induced a decrease in c-wave amplitude on ERG as well as damage to RPE/photoreceptor organelles and cells. [28][29][30][31][32][33][34] The retinotoxic effects of iodine and derivates are likely due to their strong oxidizing and reducing activity in biochemical reactions, which generate numerous free radicals and secondary DNA-base fragmentation. 27,35 In the second instance, lesser retinal damage after IfCG application may be due to the osmolarity profile.…”
Section: Subretinal Injection Of Icg and Ifcg 55mentioning
confidence: 99%